Analisis Hukum Putusan Dewan Kehormatan Penyelenggara Pemilihan Umum dalam Pelanggaran Kode Etik Penyelenggara Pemilu di Kabupaten Lombok Timur Tahun 2024 : Studi Kasus Perkara Nomor 187-PKE-DKPP/VIII/2024 - Sandy Ari Wijaya; Widya Hartati (Referendum : Jurnal Hukum Perdata dan Pidana, 2025)
Enforcement of the election organizer's code of ethics is an important aspect of maintaining the democratic process and elections in Indonesia. The integrity of election organizers is a main pillar in realizing democratic and legitimate elections. The Election Organizer Ethics Council (DKPP) has a crucial role in upholding ethical standards among election organizers. This research aims to analyze the legal aspects of the DKPP's decision regarding violations of the election organizer's code of ethics in East Lombok Regency in 2024, focusing on the case study of Case Number 187-PKE-DKPP/VIII/2024. Through a case study approach and normative juridical analysis, this research will examine the legal basis, considerations, and implications of the DKPP's decision on election organizers and the integrity of the election process at the local level, namely East Lombok Regency. The results of this research indicate that the legal analysis of the Election Organizer Ethics Council's Decision in Case Number 187-PKE-DKPP/VIII/2024, which resulted in the permanent dismissal of a member of the East Lombok Regency KPU, is based on the normative aspect and the fundamental essence of ethics and the neutrality of independent and fair election organizers without any affiliation or indication of bias towards any group or faction